Premature mortality among elderly in Malaysia, 2014 - Nazirah Alias; Mohd Azahadi Omar; Shubash Shander Ganapathy; Mohamad Fuad Mohamad Anuar; Chandrika Jeevananthan; Fazila Haryati Ahmad; Tan, Lee Ann (Penerbit Universiti Kebangsaan Malaysia, 2019)
Introduction Substantial advances on the life expectancy have been achieved in Malaysia over the past few decades. It is essential that elderly lead a healthier old age which leans towards successful aging. Thus, this study describes the major causes of premature mortality among the elderly population in Malaysia, 2014. Methods The calculation of premature mortality in terms of Years of Life Lost (YLL) was based on the method used in the Global Burden of Disease (GBD) study. YLL is the mortality component determined by the age-sex specific number of deaths and life expectancy at the age of death. Mortality data was obtained from the Department of Statistics Malaysia. Elderly aged 60 years and above were included in this study. Results The major causes of premature mortality among elderly in Malaysia were Cardiovascular and Circulatory Diseases (39.0%); followed by Malignant Neoplasms (16.6%), Respiratory Diseases (9.8%), Respiratory Infections (9.2%) and Diabetes Mellitus (6.8%). Conclusions Awareness programme, early screening and help seeking among elderly should be a priority in planning health services to reduce the burden of Non-communicable diseases (NCD) among elderly.